2017
DOI: 10.17159/sajs.2017/20160201
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting winter wheat yields using MODIS NDVI data for the Central Free State region

Abstract: Consumption of wheat is widespread and increasing in South Africa. However, global wheat production is projected to decline. Wheat yield forecasting is therefore crucial for ensuring food security for the country. The objective of this study was to investigate whether the anthesis wheat growth stage is suitable for forecasting dryland wheat yields in the Central Free State region using satellite imagery and linear predictive modelling. A period of 10 years of Normalized Difference Vegetation Index data smoothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…These periods include the flowering and grain filling periods within the phenological period of the crop. These results are consistent with studies reporting a high correlation between NDVI and yield during flowering and grain filling (Mkhabela et al, 2011, Mashaba et al, 2017, Panek and Gozdowski, 2020. The most suitable period for wheat yield estimation in the study area is flowering and grain filling periods, which corresponds to 4-6 weeks before harvest.…”
Section: Landsat-ndvi and Yield In Producer Fieldssupporting
confidence: 92%
See 2 more Smart Citations
“…These periods include the flowering and grain filling periods within the phenological period of the crop. These results are consistent with studies reporting a high correlation between NDVI and yield during flowering and grain filling (Mkhabela et al, 2011, Mashaba et al, 2017, Panek and Gozdowski, 2020. The most suitable period for wheat yield estimation in the study area is flowering and grain filling periods, which corresponds to 4-6 weeks before harvest.…”
Section: Landsat-ndvi and Yield In Producer Fieldssupporting
confidence: 92%
“…There are several studies in the literature for wheat yield estimation using linear modeling through MODIS satellite imagery. Mashaba et al (2017) found a high correlation (R 2 : 0.73) between yield and NDVI during flowering, while Lopresti et al (2015) North of Buenos Aires province, Argentina showed a good correlation (R 2 :0.52) between wheat yield and MODIS-NDVI 1 month before harvest during flowering period. A similar result was given in a national study in the USA in the relationship between NDVI data obtained from 250 m spatial and 16 day temporal resolution MODIS images and yield (R 2 : 0.51) for the period between the end of May and the beginning of June, when the vegetation reached its peak level (Jahnson, 2016).…”
Section: Modis-ndvi and Yield In Producer Fieldsmentioning
confidence: 94%
See 1 more Smart Citation
“…For Argentina, Lopresti et al (2015) find an increase of yield of 109 kg/ha with each additional point of peak NDVI as measured by MODIS data (R 2 of 0.53). For10 seasons in the 2000-2013 period from South Africa's Free State, Mashaba et al (2017) find that MODIS-based NDVI values from up to 30 days before anthesis have the highest predictive power (with an R 2 of 0.73) with a 0.1 point change in the NDVI predicted to increase wheat yield by 1.21 t/ha (from a mean of about 2.2 t/ha).…”
Section: Estimation Strategymentioning
confidence: 95%
“…Lots of studies have explored the empirical relationship between NDVI and crop yield (Mkhabela et al, 2005;Huang et al, 2014;Mashaba et al, 2017). However, different studies have used different NDVI variables, such as original NDVI, average or accumulated NDVI over the growth period, average or accumulated NDVI over key growing stages, etc.…”
Section: Introductionmentioning
confidence: 99%